Holding the Child (and Practitioner) in Mind? Youth Justice Practitioners' Experiences Supervising Young People Displaying Sexually Harmful Behavior. Issue 9 (May 2020) - Myles-Wright, Andrew; Nee, Claire
This qualitative study explored the lived experiences of youth justice practitioners supervising young people (below 18 years old) displaying sexually harmful behavior within the Youth Justice System (YJS) in the United Kingdom, as little is currently known about the challenges faced when working with this vulnerable group. Five practitioners from two Youth Offending Services (YOS) participated in individual semistructured interviews, which were subjected to thematic analysis while also analyzing the performative function of language used. The analysis identified an overarching theme of "systemic unease, " which contained two subthemes surrounding "unease with the self, and wider YOS personnel" and "unease working with partner agencies." The findings illuminate critical issues regarding future practice with this underresearched group of young people within the broader context of youth justice, which require further exploration and investigation. The "dual relationship problem" involving tension between risk management and therapeutic alliance is explored in relation to this group. The moral acquaintance model and the model of dynamic adaptation are suggested as helpful approaches to support practitioners and multi-agency professionals going forward in this area.